Cartan structure groupoids and algebroids - Fushimi, Luiz Felipe Villar (2024)
This work concerns Cartan structure algebroids, a new synthesis of two other mathematical concepts: Cartan geometries and Lie algebroids. The objective of this synthesis is to provide a generalizing framework for the development of Lie theory of algebroids, most notably that of G-structure algebroids with connection. Aside from defining these objects and establishing their initial basic properties, we explore some developments of Lie theory of algebroids in which these algebroids may be used.